Interface micromotion failure simulation of cementless hip prosthesis - Abdul Kadir, Mohammed Rafiq; Kamsah, Nazri; Tamin, Mohd. Nasir; Lee, Faisal Abidin (Faculty of Mechanical Engineering, 2007)
The most commonly reported failure modes of cementless hip stems are loosening and thigh pain; both are attributed to the relative motion at the bone-implant interface due to failure to achieve sufficient primary fixation. Accurate predictions of hip stems’ stability are therefore crucial to the pre-clinical analyses of hip arthroplasty. This study uses finite element technique to analyse the effect of muscle forces on the predicted micromotion and therefore stability of cementless femoral components. An in-house experimentally validated micromotion algorithm was used in analyses simulating two of the most common physiological activities – walking and stair-climbing. The results showed that models where muscle loads were included had ten times larger micromotion than those modelled without muscle loads. Ignoring muscle forces in any pre-clinical evaluation of femoral stems are therefore not advisable as it will overestimate the stability of the stem.